Arm Girth and Calf Girth of Government Primary School Children in Dhaka City (Bangladesh Journal of Anatomy, 2017)
Context: Body circumference measurements such as upper arm girth and calf girth are useful public health indices. Upper arm girth and calf girth can be used as an important measurement tool to assess growth of an individual. The present study was planned to determine differences in upper arm girth and calf girth between boys and girls of primary schools. Materials & Methods: A cross-sectional analytical type of study was conducted in the department of anatomy, Dhaka Medical College, Dhaka, from January 2012 to December 2012. The present study was performed on 400 government primary school children. Out of 400 children, 200 were boys and 200 were girls. The study population was divided into three groups A, B, C according to age and sex of the subject. Group A include age 9+ years, group B include age 10+ years and group C include age 11+ years old children. Each group was again subdivided into A1, B1 and C1 for boys and A2, B2 and C2 for girls. The subjects of this age group were the students of class III to class V. With the help of a standardized flexible ribbon tape measurements were recorded in cm. Arm girth was measured at the midpoint of upper arm and the maximum calf girth was measured around the calf. Results: Upper arm girth of group A1 were significantly higher (P